The Endocannabinoid Reuptake Inhibitor WOBE437 Is Orally Bioavailable and Exerts Indirect Polypharmacological Effects via Different Endocannabinoid Receptors - Reynoso-Moreno, Inés; Chicca, Andrea; Flores-Soto, Mario E.; Viveros-Paredes, Juan M.; Gertsch, Jürg (Frontiers in Molecular Neuroscience, 2018)
Different anandamide (AEA) transport inhibitors show antinociceptive and antiinflammatory effects in vivo, but due to their concomitant inhibition of fatty acid amide hydrolase (FAAH) and overall poor bioavailability, they cannot be used unequivocally to study the particular role of endocannabinoid (EC) transport in pathophysiological conditions in vivo. Here, the potent and selective endocannabinoid reuptake inhibitor WOBE437, which inhibits AEA and 2-arachidonoylglycerol (2-AG) transport, was tested for its oral bioavailability to the brain. WOBE437 is assumed to locally increase EC levels in tissues in which facilitated EC reuptake intermediates subsequent hydrolysis. Given the marked polypharmacology of ECs, we hypothesized to see differential effects on distinct EC receptors in animal models of acute and chronic pain/inflammation. In C57BL6/J male mice, WOBE437 was orally bioavailable with an estimated tmax value of ≤20 min in plasma (Cmax ∼ 2000 pmol/mL after 50 mg/kg, p.o.) and brain (Cmax ∼ 500 pmol/g after 50 mg/kg, p.o.). WOBE437 was cleared from the brain after approximately 180 min. In addition, in BALB/c male mice, acute oral administration of WOBE437 (50 mg/kg) exhibited similar brain concentrations after 60 min and inhibited analgesia in the hot plate test in a cannabinoid CB1 receptor-dependent manner, without inducing catalepsy or affecting locomotion. WOBE437 significantly elevated AEA in the somatosensory cortex, while showing dose-dependent biphasic effects on 2-AG levels in plasma but no significant changes in N-acylethanolamines other than AEA in any of the tissues. In order to explore the presumed polypharmacology mediated via elevated EC levels, we tested this EC reuptake inhibitor in complete Freud’s adjuvant induced monoarthritis in BALB/c mice as a model of chronic inflammation. Repetitive doses of WOBE437 (10 mg/kg, i.p.) attenuated allodynia and edema via cannabinoid CB2, CB1, and PPARγ receptors. The allodynia inhibition of WOBE437 treatment for 3 days was fully reversed by antagonists of any of the receptors. In the single dose treatment the CB2 and TRPV1 antagonists significantly blocked the effect of WOBE437. Overall, our results show the broad utility of WOBE437 for animal experimentation for both p.o. and i.p. administrations. Furthermore, the data indicate the possible involvement of EC reuptake/transport in pathophysiological processes related to pain and inflammation.